Sufficient conditions for the almost layer finiteness of groups - Senashov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We prove a theorem that describes almost layer-finite groups in the class of conjugatively biprimitive-finite groups.